The power of six - Lore, Pittacus (New York : Harper & Row Publishers, Inc., 2011)
I've seen him on the news. Followed the stories about what happened in Ohio. John Smith, out there, on the run. To the world, he's a mystery. But to me . . . he's one of us. Nine of us came here, but sometimes I wonder if time has changed us - if we all still believe in our mission. How can I know? There are six of us left. We're hiding, blending in, avoiding contact with one another...but our Legacies are developing, and soon we'll be equipped to fight. Is John Number Four, and is his appearance the sign I've been waiting for? And what about Number Five and Six? Could one of them be the raven-haired girl with the stormy eyes from my dreams? The girl with powers that are beyond anything I could ever imagine? The girl who may be strong enough to bring the six of us together?
Keywords: MYSTERY -- FICTION